Analisis Multi Akad dalam Pembiayaan Hybrid KPR-Inhouse pada Industri Perumahan PT. Karya Cipta Sakinah Perspektif Ekonomi Syariah - Qaidul Muttaqin; Ahmad Djalaluddin; Masyhuri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this research is to analyze the elements of multiple contracts in the application of the KPR-Inhouse hybrid financing model in the housing industry of PT Karya Cipta Sakinah, Paiton Probolinggo District as well as the obstacles and prospects in its application. The method used is qualitative with the type of field research. Researchers focus on the results of data collection from predetermined informants. The results showed that the hybrid financing system that combines the murabahah contract in the Sharia KPR and the ba'i taqsith contract in the inhouse scheme, is not included in the multi-contract category because each contract stands alone. The main obstacle to its implementation is the low Islamic financial literacy among the public, which limits the understanding and acceptance of this model. However, this system has positive prospects to support Islamic financial inclusion as it can reach community groups that are underserved by formal banks. This system has the potential to be adopted by more housing developers and contribute to the expansion of access to Islamic finance in Indonesia.